(untitled) (Medicine Today, 2013)
Tuberculosis of spine is common for Bangladesh. Imaging modality is importent for diagnosis of it.Forty-Six clinically suspected tubeculous spondylitis patient were included in this prospective, consecutive study during July 2003 to June 2005. Among them, 42 cases of MRI and histology proven were included in the article. The peak incidence was found to be in 3rd decade (43.48%) with male predominance, 2.5 times more than female. The mean age was revealed 33.3 years. Highest occurrence was in double vertebrae involvement (42.86%) along with continuous vertebral involvement (85.71%). Destruction & collapse found in most case (88.10%) with predominance with posterior element involved (54.76%). Spinal deformity was least (11.90%). Para-spinal soft tissue involvement was found in most cases ((80.95%) with no calcification. 21.43% shows cord compression. MRI was found sensitive and accurate modality for diagnosis of TB spondylitis. DOI: http://dx.doi.org/10.3329/medtoday.v24i2.15007 Medicine Today 2012 Vol.24(2): 59-62